Pengembangan Media Pembelajaran Berbasis Mobile Learning untuk Memahami Teks Prosedural - Giri Indra Kharisma (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2019)
A mobile-learning based media is a learning media using android applications to deliver materials about the concept of procedure text for eighth graders of junior high school. The design model of Research and Development used is adapted from R2D2 and ASSURE to produce an efficient, attractive, and effective. Based on the results of product trials and field tests, it is evident that this learning media is able to foster enthusiasm or passion for student learning. This is because this learning media presents procedure text material along with interesting features to support the procedure text learning. The feature consists of sample procedure videos, online learning groups, KBBI online to search for word meanings, and quizzes to find out students' understanding.